Addressing the quality of communication with older cancer patients with cognitive deficits: Development of a communication skills training module. Issue 4 (August 2020) - Korc-Grodzicki, Beatriz; Alici, Yesne; Nelson, Christian; Alexander, Koshy; Manna, Ruth; Gangai, Natalie; Shen, Megan J.; Parker, Patricia A.; Banerjee, Smita C.
Abstract: Objective: Effective communication is an essential part of patient-centered care. The complexity of cancer care in older adults makes communication challenging, particularly when older patients have cognitive deficits and lose their autonomy. This paper describes the development, implementation, and evaluation of a communication skills training module for health care providers (HCPs) who work with older adults with cancer, with or at risk of developing cognitive deficits. Method: Using a pre-post single arm study design, 99 HCPs from a comprehensive cancer center in North-East USA, who worked primarily with geriatric patients, participated in the study. Participants included Advance Practice Providers (including Nurse Practitioners and Physician Assistants; n = 24, 24.2%); nurses ( n = 23, 23.2%), social workers ( n = 14, 14.1%), physicians ( n = 13, 13.1%), and "other" HCPs (including occupational therapists, physical therapists, and psychologists; n = 20, 20.2%). The HCPs participated in a one-day geriatric communication skills training program in groups of 12–15 over a 2-year period. Participants complete pre-post surveys on module evaluation and perception of self-efficacy as well as pre-post video-recorded Standardized Patient Assessment (SPA) to evaluate communication skill uptake. Results: Most participants evaluated the module positively; over 90% indicated that they agreed or strongly agreed with five of the six module evaluation items. HCPs' self-efficacy in communicating with cancer patients with cognitive deficits significantly increased from pre- to post-module training. There was a significant increase in the following communication skill use from pre- to post-training: checking patient preferences, declaring agenda, and inviting agenda. Significance of results: Results demonstrated a successful implementation of the program as evidenced through favorable program evaluation, significant gains in self-efficacy, as well as significant improvement in several communication skills.